Supply Chain Management Information System for Vaccines Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
An academic article title is supply chain management information system for vaccines management in Thailand aim to present for vaccines management in Thailand for better effective The vaccines management needs need to be injected boost immunity. The processes consisted of Seller, Manufacture, Distribution, and Customers ,All component connect with information communication technology in the Thailand with the supply chain. This truly added the immunity in Thailand. The supply chain and information system may be used to manage vaccines.